PENGARUH SET KESEMPATAN INVESTASI TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL DAN IMPLIKASINYA PADA RETURN SAHAM - , NUR ASHARI HIJRAH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examined the effect of the investment opportunity set on the disclosure of intellectual capital and its implications on stock returns. Sample consists of 88 firms from Pharmaceutical, Telecommunications, Computers and Electronics, Media & Publications, Food & Beverage, and Automotive industries that listed in Indonesia Stocks Exchange from 2007 to 2009. The results of this study found evidence that the investment opportunity set has negative effect on the disclosure of intellectual capital and significant, indicating that companies with high growth opportunities will tend to not disclose some of its intellectual capital. Disclosure of intellectual capital has no effect on the stock returns suggests that investors do not respond to information the disclosure of intellectual capital. Investment opportunity set has a positive effect on stock returns and significant. This means that when companies make an investment, it is becoming positive information to investors because the company's growth.